Impact of Sensitization and Inflammation on the Interaction of Mast Cells With the Intestinal Epithelium in Rats - Becker, Jasmin; Ott, Daniela; Diener, Martin (Frontiers in Physiology, 2019)
The density of intestinal mast cells has been reported to increase during inflammatory bowel disease (IBD). As mast cell mediators are known to increase the permeability of epithelial tight junctions, we hypothesized that antigen responses in sensitized animals might be enhanced under inflammatory conditions. This would contribute to a vicious circle by further enhancing the entry of luminal antigens into the colonic wall and thereby continuing the inadequate immune response during IBD. Therefore, one group of rats was sensitized against ovalbumin. In a second group of animals additionally a colitis was induced by rectal administration of 2,4,6-trinitrobenzenesulfonic acid (TNBS) dissolved in ethanol. Specimens from distal colon and jejunum (as intestinal segment located distantly from the inflamed area) were mounted in Ussing chambers to measure tissue conductance, short-circuit current (Isc) induced by antigen exposure and paracellular permeability (fluorescein flux). This was paralleled by determination of mast cell markers and tight junction proteins with immunofluorescence and qPCR. In contrast to the initial hypothesis, antigen-induced Isc was not upregulated, but tended to be downregulated in the tissues from the colitis animals, both in colon and in jejunum. Only in the jejunum mast cell degranulation evoked an increase in fluorescein flux. Mast cell density was not altered significantly in the colon of the colitis animals. In the jejunum, sensitization induced a strong increase in mast cell density, which was unaffected by additional induction of colitis. Expression of sealing tight junction components claudin-3 and -4 were increased on the protein level in the sensitized animals in comparison to non-sensitized animals. Additional induction of colitis evoked a downregulation of claudin-3 in both intestinal segments and an upregulation of claudin-4 in the jejunum. Consequently, these data indicate segment differences in mast cell - epithelium interaction, but no enhancement of ion secretion in the TNBS/ethanol model of acute colitis after prior sensitization.